Exploring the potential of highly efficient Graphite/Chitosan-PVC Composite Electrodes in the Electrochemical Degradation of Reactive Red 4 - Mohd Halim, Nadhra H; Adnan, Rohana; Lahur, Azizul H; Nordin, Norazzizi (Society of Chemical Industry, 2021)
BACKGROUND: Previous reported studies revealed that composite electrodes are effective and suitable for wastewater treatment applications owing to their high porosity and increased electrochemical active area. However, the critical challenges to the wider adoption of composite electrodes for environmental applications are the need to reduce the cost of electrode materials, and to improve both their long-term stability and electrocatalytic performance. This study aims to investigate the efficiency and stability of low-cost graphite/chitosan-polyvinyl chloride (C/Chi-PVC) composite electrodes for Reactive Red 4 (RR4) degradation. Toxicity of the treated RR4 wastewater also was investigated using a seed germination test. RESULTS: A cyclic voltammetry study conducted revealed that C49/Chi21-PVC30 (49% C, 21% Chi, 30% PVC) showed better electrochemical behaviour for hypochlorous ion (OCl−) formation, which is responsible for RR4 degradation via indirect electrochemical reaction. Owing to the synergistic effect of both materials, high colour, total organic carbon (TOC) and chemical oxygen demand (COD) removals of 99.61%, 89.68% and 76.35%, respectively, were achieved with less electrode damage at optimum electrolysis parameters. The treated RR4 solution displayed low toxicity after 14 days of exposure to the water sample. The electrode stability in the aggressive OCl− solution was studied by characterization of fresh and used electrodes using field emission scanning electron microscopy with energy-dispersive X-ray spectroscopy (FESEM-EDX). This showed no significant difference in surface roughness and elemental composition; the reusability test confirmed that the electrode can be applied in repeated electrolysis. CONCLUSION: Overall, the fabricated electrode in this study showed high efficiency with robust and durable characteristics for wastewater treatment applications.